The new climate fund for loss and damage of the Paris Agreement: discussions on financing and climate justice - Matheus Freitas Rocha Bastos; Wânia Duleba (Revista Brasileira de Política Internacional)
Abstract Discussions on losses and damages caused by climate change have gained momentum with the creation of a dedicated fund at COP 27. This article, based on literature review and analysis of UNFCCC documents, traces the trajectory of these discussions in the multilateral climate change regime, from 1992 to the operationalization of the fund at COP 28. The research analyzes key challenges for the first year of the fund’s board and the growing importance of climate justice in the international agenda. Despite the significant progress, there are still critical gaps to be filled, such as defining clear criteria for climate vulnerability and resource mobilization.